Towards a Coherent Theory of Project Alliancing: Discovering the System’s Complex Mechanisms Yielding Value for Money (Construction Economics and Building, 2017)
Alliancing is a relatively new construction project delivery method receiving increasing interest globally while also eliciting many questions about its effectiveness. That is why its operating logic should be clarified beyond the currently existing general views. Correspondingly, this paper aims to define the means and mechanisms which influence the capacity of alliancing to produce value for money. The work establishes the interlaced impact chains between formal basic solutions of alliancing and the key result areas defining the value-for-money ratio. This is made by focussing on a single alliance project and its procedural solutions and experiences. The case project of the study was an urban road tunnel under a city structure and the impact chains were explored by interviewing all eight members of the alliance leadership team covering all contracting parties. The two-stage personal interviews were conducted in accordance with the systematic modelling procedure resulting in eight cognitive maps which were then combined into a group map. The resulting model included around one hundred interlinked concepts initially, but was streamlined for the paper. Accordingly, alliancing offers a concrete framework which gives better than normal chances of success in the case of complex, challenging projects fraught with much uncertainty. Many diverse basic alliance solutions/features contribute to success, while each feature also seems to strengthen the impact of the others. This suggests that, at its best, pure project alliance is not only a coherent but also a holistic solution to challenging projects.